The role of religious orientation in the business performance of women owned firms: a preliminary study in Malaysia halal food industry - Tahir, Ida Rizyani; Abdul, Mohani (Macrotheme Capital Management, 2013)
This paper examines the relationship between religious orientation and firm performance for women and men-owned small medium firms in the Malaysia halal food industry. In this preliminary study, results indicate that religious orientation variable had a positive impact on the business performance of men and women-owned firms. The relationship was investigated using Pearson product-moment correlation coefficient. There was a weak, positive correlation between the two variables. An independent samples t-test was conducted to compare the religious orientation scores for males and females. There was a significant difference in scores for males and females. These findings suggest that the growth aspirations for women-owned firms may be driven by factor other than religious orientation as compared to men-owned firms.